IMPLEMENTATION OF THE SYSTEM WWS IS THE REQUIREMENT IN DEVELOPMENT OF ELECTROMOBILITY - Polakowski, Krzysztof (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Rapidly is growing negative impact of toxic emissions of internal combustion engines (used in road transport), on the ecosystem. Apart from the problems associated with air pollution and the environment at the stage of extraction, transport and processing of liquid and gaseous hydrocarbon fossil fuels, the biggest problem is with the mass poisoning the atmosphere by products emanating from the exhaust pipes of all (land, sea and air) means of transport. Electric drive can be an effective remedy for these negative effects. Electric motors are practically emission-free and in terms of efficiency, in the conversion electrical energy into mechanical, three times superior to heat engines. In order electric trucks have been fully ecological, energy required to charge the energy containers, in the form of electrochemical batteries, must come from renewable energy sources. The basic condition for the development of electromobility based on the electric car is the need for widespread and rapid transition to production of electricity from carbon-free renewable energy sources: wind, water and sun. Published (by one of the world’s leading scientific centers) results of research and analyzes show that there is a real chance to create an alternative (to the traditional system of generating electricity, based mainly on thermal power plants burning fuels), the new zero-emission system WWS (Wind, Water, Sun), based on the use of the energy contained in the wind, flowing water, and solar radiation. The presented data show that there is a real chance of transition to WWS in the next 30 – 50 years.